Specific Inhibition of Brain Angiotensin III Formation as a New Strategy for Prevention of Heart Failure After Myocardial Infarction. Issue 2 (February 2019) - Leenen, Frans H. H.; Ahmad, Monir; Marc, Yannick; Llorens-Cortes, Catherine
Abstract : Aims: Inhibition of brain angiotensin III by central infusion of aminopeptidase A (APA) inhibitor firibastat (RB150) inhibits sympathetic hyperactivity and heart failure in rats after myocardial infarction (MI). This study evaluated effectiveness of systemic treatment with firibastat compared with AT1 R blocker, losartan. Methods and Results: MI was induced by ligation of left coronary artery in male Wistar rats. Rats were treated from 1 to 5 weeks after MI in protocol 1 with vehicle, or firibastat at 50 mg/kg/d subcutaneously (s.c.) or 150 mg/kg/d oral, once daily, and in protocol 2, with vehicle, firibastat 150 mg/kg or losartan 50 mg/kg oral twice daily. At 5 weeks, left ventricle function was evaluated by echocardiography and Millar catheter. After MI, rats developed moderate severe heart failure. Both s.c. and oral firibastat inhibited brain APA and attenuated left ventricle dysfunction. Oral firibastat and losartan similarly improved left ventricular end diastolic pressure. However, whereas firibastat improved dP/dtmax, losartan lowered dP/dtmax and left ventricular peak systolic pressure, and increased plasma creatinine by 50%. On the other hand, losartan more effectively inhibited cardiac fibrosis. Conclusion: Inhibition of the brain renin–angiotensin system by oral APA inhibitor is at least as effective as oral AT1 R blocker to inhibit cardiac dysfunction after MI but without hypotension or renal dysfunction.